Pengaruh Kepuasan dan Kepercayaan Terhadap Loyalitas Konsumen Toko Central Muslim Bima - Didan Dharmawan; Muhajirin; Mulyadin (Teewan Journal Solutions, 2024)
This research aims to determine the influence of satisfaction and trust on consumer loyalty at the Central Muslim Bima Store. The type of research used is associative. The research instrument used in this research was a Likert scale questionnaire and each statement item in the questionnaire was given a weight of 1-5. The population used in this research is all consumers who have purchased and used the services of the Bima Central Muslim Shop, the exact number of which is unknown (Unknown Population). To determine the number of samples in an unknown population, the Cochran formula was used and a sample of 50 people was obtained. The sampling technique was carried out using the purposive sampling method. The data collection techniques used in this research are observation, questionnaires and literature study. The data analysis techniques used to process data in this research are validity tests, reliability tests, classical assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests. Then proceed with multiple linear regression analysis, correlation coefficient, determination test, t test and f test. The results of the research show that there is an influence of satisfaction and trust on consumer loyalty at the Central Muslim Bima Store.